PENGARUH TRANSFER PELATIHAN, MOTIVASI, DAN GAYA KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA KARYAWAN (Studi Pada Dosen Fakultas Ekonomi dan Bisnis Universitas Katolik Soegijapranata Semarang) - Najib, Abayakla Muhammadin; Darmastuti, Ismi; Wicaksono, Bimo Suryo (Faculty of Economics and Business Diponegoro University, 2023)
ABSTRACT Over the last few years it has been known that there is a lack of employee performance at Fakultas Ekonomi dan Bisnis Universitas Katolik Soegijapranata Semarang. The phenomenon and the differences in the results of research on transfer of training, motivation, and transformational style of leadership are the basis of the problem why this research was conducted. This study uses primary data obtained from direct interviews and distributing questionnaires to 100 respondents. This study used multiple linear regression analysis resulted in the finding that transfer of training has a significant positive effect on employee performance, motivation has a significant positive effect on employee performance, and transformational leadership style has a positive and significant effect on employee performance